2020
DOI: 10.1037/cou0000364
|View full text |Cite
|
Sign up to set email alerts
|

Dyadic, longitudinal associations among outcome expectation and alliance, and their indirect effects on patient outcome.

Abstract: Research indicates that patient outcome expectation (OE) correlates with improvement, and that this association may be mediated by better patient-therapist alliances. However, despite OE and alliance being dyadic and dynamic constructs, most research on these direct and indirect associations has assessed these variables from only one dyad member’s perspective and at single time points. Addressing these gaps, we used a longitudinal actor-partner interdependence model to first examine OE-alliance associations. N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
38
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 40 publications
3
38
1
1
Order By: Relevance
“…Looking at the therapist effect (Hypothesis 4), results showed that therapists themselves explain a significant proportion (9%) of the variance in patients’ outcome expectation change scores. These results are consistent with the findings of Vîslă and colleagues (2019) and Constantino, Aviram, and colleagues (2020) that also showed therapists differences in their patients’ outcome expectation. Moreover, these results are consistent with previous findings from clinical trial and naturalistic data, showing that 5–10% of outcome variance can be explained by differences between the therapists (Firth et al, 2019; Johns et al, 2019; Kim et al, 2006).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Looking at the therapist effect (Hypothesis 4), results showed that therapists themselves explain a significant proportion (9%) of the variance in patients’ outcome expectation change scores. These results are consistent with the findings of Vîslă and colleagues (2019) and Constantino, Aviram, and colleagues (2020) that also showed therapists differences in their patients’ outcome expectation. Moreover, these results are consistent with previous findings from clinical trial and naturalistic data, showing that 5–10% of outcome variance can be explained by differences between the therapists (Firth et al, 2019; Johns et al, 2019; Kim et al, 2006).…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, future studies need to replicate these findings, and then test additional predictors at the patient and therapist level, or the interaction between these two levels. Such variables could represent change in other patient process variables during the therapy, therapist’s characteristics and responsiveness (Stiles & Horvath, 2017; Wu & Levitt, 2020); and dyadic interactions (Constantino et al, 2020). Limitations aside, the present study contributed to the much-needed information on the pattern of change in patient outcome expectation, as well as on participant correlates of both early positive outcome expectation and outcome expectancy trajectory of change during treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In this framework, the TA is a dyadic process in which clients and therapists mutually influence one another [3]. Although most studies to date have examined the client's perspective on the TA [4], recently there has been growing interest in the therapist's perspective as well [1], allowing for an investigation of their agreement/ discrepancies: that is, the mean difference between client-therapist TA ratings [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Given the empirical support, it is perhaps unsurprising that patient outcome expectations have become an increasing area of research focus. To name just a few diverse areas, researchers have examined mediators of the outcome expectation-outcome link (Constantino et al, 2020), therapist attunement to patient expectancies over time (Coyne et al, 2020) and experimental tests of explicit therapist persuasion strategies that can foster more positive outcome expectancies . Yet, despite this evolving research base, relatively little work has examined what gives rise to more positive or negative outcome expectations in patients.…”
Section: Introductionmentioning
confidence: 99%